Global Stability of an SEIRS Model with Impulsive Vaccination and Saturating Incidence Rate - Yang Yang; Cheng Nannan (Institute of Advanced Engineering and Science, 2014)
This paper introduces a impulsive vaccination SEIRS epidemic model with constant input, saturation incidence rate and exposed period, and the threshold valueσ=1 is obtained at which disease is eliminated. By using the impulsive differential equation theory, it is proved that whenσ<1, the disease-free periodic solution is globally asymptotically stable, and that whenσ>1,the system is uniformly persistent. On these grounds, it is shown that impulsive vaccination can bring obvious effects on the dynamics behaviors of the system.